Dynamics of Wildlife Conflict in West Sumatra by Balai Konservasi Sumber Daya Alam (BKSDA) of West Sumatra in 2022-2023 - Annisa Putri Anggraini; Lugina Mindasari; Rijal Satria (Microbiotech, 2025)
Human-wildlife conflict is a negative interaction between humans and wildlife that has an impact on life, economy, culture, conservation efforts and the environment that can lead to negative perspectives of humans towards wildlife. This study aims to assess the dynamics of human-wildlife conflicts in West Sumatra in 2022-2023 and evaluate the role of the Balai Konservasi Sumber Daya Alam (BKSDA) West Sumatra in handling these conflicts. The data was collected from BKSDA as Secondary data analysis methods and direct interviews. The Human-wildlife conflict cases were analyzed and confirmed in 14 species, with the highest intensity in Sumatran Tiger (Panthera tigris sumatrae), Estuarine Crocodile (Crocodylus porosus), and Sun Bear (Helarctos malayanus). The conflicts are distributed in 66 sub-districts,12 of the 19 districts/cities in West Sumatra. We assumed that these conflicts were triggered by forest encroachment, agricultural land expansion, and habitat degradation. The BKSDA of West Sumatra responds to these conflicts by implementing conflict management, including patrols, animal security, deterrence, and counseling to the community in the involvement of conservation efforts, which proved effective in reducing conflict intensity.